Positive Solution of Elliptic Systems Involving Critical Growth (Journal of Partial Differential Equations, 2020)
In this paper, we consider the asymptotic behaviour of the positive solution of elliptic systems with critical growth and obtain the growth rate.
Keywords: Radiation singular solution; critical growth